DNA Structural Barcode Copying and Random Access. Issue 5 (22nd February 2021) - Bošković, Filip; Ohmann, Alexander; Keyser, Ulrich F.; Chen, Kaikai
Abstract : Digitally encoded deoxyribonucleic acid (DNA) nanostructures built via DNA self‐assembly have established applications in multiplexed biosensing and storing digital information. However, a key challenge is that DNA structures are not easily copied which is of vital importance for their large‐scale production and access to desired molecules by target‐specific amplification. Herein, DNA structural barcodes are built and the copying and random access of the barcodes from a library of molecules is demonstrated using a modified polymerase chain reaction (PCR). The structural barcodes are assembled by annealing a single‐stranded DNA scaffold with complementary short oligonucleotides containing protrusions as digital bits at defined locations. DNA nicks in these structures are ligated to facilitate barcode copying using PCR. To randomly access a target from a library of barcodes, a non‐complementary end in the DNA construct that serves as a barcode‐specific primer‐template is used. Readout of the DNA structural barcodes is performed with nanopore measurements. The study provides a roadmap for the convenient production of large quantities of self‐assembled DNA nanostructures. In addition, this strategy offers access to specific targets, a crucial capability for multiplexed single‐molecule sensing, and DNA data storage. Abstract : A method to copy deoxyribonucleic acid (DNA) structural barcodes and to randomly access the target barcode using a polymerase chain reaction (PCR)‐based assay is demonstrated. The approach facilitates applications in multiplexed biosensing and for DNA data storage and creates a roadmap for the convenient production of large quantities of self‐assembled DNA nanostructures.